Implantação do Parque Aqüícola do Braço do Rio São Francisco Verdadeiro, Reservatório de Itaipu, Paraná, Brasil - Maranhão, Taciano Cesar Freire (2010)
The study was analyzed the standard regulatory conditioned to transfer used of Union’s water, teh historic physical, chemical and biological data for water quality, criteria for aquaculture park selecting áreas and its carryng capacity of the water of the São Francisco Verdadeiro in the Itaipu’s Reservoir that hás great potential of cultivation of fish in the network tank prodution system. The principal objective is to analyse the results of water sample during the predeployment, deployment and post deployment of aquaculture parks, from February 1998 to December 2010. Phisical, chemical dada and biological agents in the three phases of implementation were collected and analyzed by IAP and offered by the Itaipu Binational. Data analysis, interpretation and its comparison with CONAMA no. 357/05 indicated that during the three phases the media were stayed within the limits. However, the analysis of variance showed no statistical difference between the periods except for the transparency, Kjeldalh nitrogen and chlorophyll “a”. The calculation of bearing capacity determined na estimate of 20 ton/year is 0,017 mg/L P. In regarding to the Decree no.4895, of November 25, 2003, about the use of physical space of the water body under federal and reinforced by the Normative Interministerial no. 06 of May 31, 2004, indicated the necessary of na ongoing discussion regarding the conflict redution between either state or federal standars regarding the compatibility of qualitative and quantitative data regarding the deployment of tanks network in Parana State.